School Cultural: Implication of Artifacts and Collegiality on Students’ Academic Performance in Public Boarding Secondary Schools in Kenya - Sagwe, George K.B.M; Ajowi, Jack Odongo; Mwebi, Bernad (International Journal of Novel Research in Education and Learning, 2016)
In Kisii Central Sub County, few secondary schools have been perennially associated with good performance whereas majorities are attributed to low students’ academic performances irrespective of the cream admission and top boarding status. These disparities in public boarding secondary schools are attributed to unique school’s cultures adopted by each school that affects and guides behaviours of the entire school population positively or negatively. A culture helps members to understand the environment and determine how to respond to the values, beliefs and norms of the organization manifested by artifacts, collegiality, norms, ceremonies and rituals. The purpose of this study was to establish implication of school culture artifacts on students’ academic performance in public boarding secondary schools in Kisii Central Sub County. The study objectives were to: Establish implication of school artifacts and Analyse implication of collegiality on students’ academic performance. The study employed a structural-functionalist approach to Organizational Culture rooted by Malinowski, Radcliffe-Brown, Parsons, and Schein. Related literature was reviewed in line with the research objectives and guided by research questions. Concurrent Nested design employing Mixed Method Approach was adopted and utilized for this study. This study was conducted in Kisii Central Sub County in public boarding secondary schools. The target population was made up of 7 principals, 49 HODs, 80 class teachers, 164 student leaders, 7 BOM chairpersons and 7 PA chair persons. Saturated sampling was used to obtain a sample population constituting; 6 Principals, 42 HODs, 72 class teachers, 144 student leaders, 6 BOM chairpersons and 6 PA chair persons. Data collection instruments were Questionnaires, Interviews schedules, FGDs, Document analysis and Observation protocol. Reliability was addressed through piloting in 1 school which was randomly sampled from the target schools and test- retest was employed together with McMillan and Schumacher strategies to establish reliability and validity. Validity of instruments was further enhanced through expert vetting by two supervisors. Descriptive statistics such as frequencies and percentages was used to describe and summarize quantitative data in form of tables to show trends. Thematic analysis was used to analyze qualitative data and focused on the discussion of the themes and sub-themes as they emerged. The findings of the study are hoped to benefit researchers, principals, MOEST as it would be a source of knowledge on the implication of school culture on students’ academic performance. The study identified that school artifacts alone do not fully in isolation influence students’ academic performance but in collaboration with other factors. It was established that collegiality influence the conduct and commitment of teachers through dialogue, consultation, sharing responsibilities, privileges and teachers’ welfare and extension students’ academic performance. The study recommended that school principals should engage the input of other stakeholders in all school activities geared towards shaping school culture for them to succeed. The study concluded that positive personal attributes of the principal combined with effective instructional, managerial, and collegial leadership and well-choreographed artifacts have implications on academic performance. The study recommended that there is need for replication studies in other contexts and settings to establish if the findings of this study are robust and to identify any differences based on contexts for generalization and adoption.
Keywords: School Culture; Artifacts; School environment; School climate